Women on Boards of Directors and their Contribution to the Risk Performance of UK Listed Firms: An Empirical Analysis. - Petrakka, Chrystalleni (2012)
This paper examines the relationship between women directors and stock volatility for British Public Listed Companies. In order to investigate our topic and quantify the relationship among the proportion of women in boardrooms and firmï¿½s risk measure, an unbalanced panel of the top 100 UK FTSE companies annual data is used for a five year period from 2007 to 2011. As risk measurement, the standard deviation of monthly stock returns separately for each year, over the five years of observation, called volatility is chosen and as the indicator of women presence on the directory boards the fraction of female directors over the total number of directors was used. This study provides new evidence suggesting that increasing the women proportion on boards up to a fixed percentage, leads to less volatile stock performance and thereby to more effective risk management. Following the fact that the European Union is currently deciding if new quotas regarding the proportion of women on boards of Public Companies will be imposed. Our evidence can shed some light on whether such a decision will be effective for European Corporations.